Storage of Text Messages on e-Book Files using Least Significant Bit and Haar Wavelet Method - Muhaimin Hasanudin; Deni Kuswoyo; Boy Yuliadi (Graduate Program of Syiah Kuala University, 2021)
This study uses the technique of incognito data and information into a container in the form of images combined with the addition of the password by using the method of Least Significant Bit (LSB) and the method of Haar Wavelet. Testing the system by sending a message in the form of a text file and an image file with the process of the original image are transformed to wear haar wavelet divided into four zones of frequency, namely LL, LH, HL and HH. Where Bit-bit Readings are planted in a zone LL and attempted insertion of the bit of the file reading into the last bit in each byte of the image file as well as can show you back the results of the message. The results of the research, i.e. images that have been processed by the method of LSB and Haar Wavelet does not change the file size, resolution, dpi and physical form image. The advantage of this method is very simple computing, oriented computers, which need less space to store and time efficient.